Financial Statement Performance for Decision Making in Granting credit Facilities - Evi Yuniarti; Anita Kusuma Dewi (Politeknik Negeri Lampung, 2012)
Financial statement analysis is an important aspect that can be used as a guideline by creditors to decide clients’ credit feasibility for business capital. This analysis can be used to determine a company’s financial performance. Based on the financial ratio analysis of the data in the financial statement, a credit institution can analyze the company’s business progress and setback. This is very useful for the decision-making process in determining the debtor’s eligibility for fund. Financial statement analysis is an instrument to observe company’s financial performance. A creditor can study a company’s business progress and setback. Keywords: financial ratio, performance measurements, decision making